Characterization of Reproductive Microbiota of Primiparous Cows During Early Postpartum Periods in the Presence and Absence of Endometritis - Kudo, Hayami; Sugiura, Tomochika; Higashi, Seiya; Oka, Kentaro; Takahashi, Motomichi; Kamiya, Shigeru; Tamura, Yutaka; Usui, Masaru (Frontiers in Veterinary Science, 2021)
Endometritis has a major impact on fertility in postpartum dairy cows. Since previous studies showed an association between reproductive microbiota and perinatal disease, we monitored both bovine uterine and vaginal microbiota in primiparous cows to elucidate the effect of early postpartum microbiota on endometritis. Uterine and vaginal samples were collected at time points from pre-calving to 35 days postpartum (DPP), and analyzed by 16S rRNA sequencing, combined with ancillary bacterial culture. A total of 7 healthy cows and 7 cows diagnosed with endometritis on 35 DPP were used in the current study. The uterine and vaginal microbiota showed a maximum of 20.1 % shared amplicon sequence variants (ASVs) at linked time points. 16S rRNA based analysis and traditional culture methods revealed that Trueperella showed a higher abundance in both uterus and vagina of the endometritis group compared to the healthy group on 21 DPP (U-test p < 0.05). Differential abundance analysis of the uterine microbiota showed that Enterococcus and six bacterial genera including Bifidobacterium were unique to the healthy group on the day of calving (0 DPP) and 28 DPP, respectively. In contrast, Histophilus and Mogibacteriaceae were characteristic bacteria in the vagina pre-calving in cows that later developed endometritis, suggesting that these bacteria could be valuable to predict clinical outcomes. Comparing the abundances of bacterial genera in the uterine microbiota, a negative correlation was observed between Trueperella and several bacteria including Lactobacillus. These results suggest that building an environment where there is an increase in bacteria that are generally recognized as beneficial, such as Lactobacillus, may be one possible solution to reduce the abundance of Trueperella and control endometritis.